Effect of Drying Process and Storage Temperature on Probiotic Lactobacillus casei in Edible Films Containing Prebiotics - Phovisay, Somsay; Siriwoharn, Thanyaporn; Surawang, Suthat (Food and Applied Bioscience Journal, 2018)
Incorporation of probiotics in edible film containing prebiotics is a novel approach for product development with potential usage in various functional food applications. The challenge of probiotic film is an ability to maintain adequate probiotic cultures throughout processing and storage. This study aimed to investigate the effect of various prebiotic edible films on the surviving rate of Lactobacillus casei TISTR 1463 during storage (4°C and room temperature). Each film consisted of L. casei TISTR 1463 (10–10 log CFU/mL) and 4% (w/v) prebiotic source (sodium alginate, gum arabic, konjac flour, pectin, or inulin). Film properties and survival rate of L. casei TISTR 1463 were monitored during storage every 5 d and shelf life prediction was calculated. Type of prebiotics significantly influenced the survival of L. casei and film strength after drying process (p<0.05). Film containing inulin had the highest survival retention of viable culture (87.4%) followed by sodium alginate (83.6%), konjac flour (80.3%), gum arabic (80.0%), and pectin (47.6%), respectively. Storage temperature also affected stability of the probiotic in prebiotic films (p<0.05). The viable cultures in sodium alginate, gum arabic, and inulin films had shelf life prediction of over 100 d at 4°C, whereas those stored at room temperature lasted for 5 day.